A new depsidone from the twigs of Garcinia Cowa - Cheenpracha S. (2014)
A new depsidone, cowadepsidone (7), along with six known xanthones (1-6) were isolated from the twigs of Garcinia cowa. Their structures were determined on the basis of spectroscopic methods. The cytotoxicity against KB, MCF-7 and NCI-H187 cancer cell lines of compounds 2-7 were also reported. © The Japan Institute of Heterocyclic Chemistry.